Creating morphological diversity in reptilian temporal skull region: A review of potential developmental mechanisms. Issue 1 (17th October 2022) - Tokita, Masayoshi; Sato, Hiromu
Abstract: Reptilian skull morphology is highly diverse and broadly categorized into three categories based on the number and position of the temporal fenestrations: anapsid, synapsid, and diapsid. According to recent phylogenetic analysis, temporal fenestrations evolved twice independently in amniotes, once in Synapsida and once in Diapsida. Although functional aspects underlying the evolution of tetrapod temporal fenestrations have been well investigated, few studies have investigated the developmental mechanisms responsible for differences in the pattern of temporal skull region. To determine what these mechanisms might be, we first examined how the five temporal bones develop by comparing embryonic cranial osteogenesis between representative extant reptilian species. The pattern of temporal skull region may depend on differences in temporal bone growth rate and growth direction during ontogeny. Next, we compared the histogenesis patterns and the expression of two key osteogenic genes, Runx2 and Msx2, in the temporal region of the representative reptilian embryos. Our comparative analyses suggest that the embryonic histological condition of the domain where temporal fenestrations would form predicts temporal skull morphology in adults and regulatory modifications of Runx2 and Msx2 expression in osteogenic mesenchymal precursor cells are likely involved in generating morphological diversity in the temporal skull region of reptiles. Abstract : Reptilian skull morphology is highly diverse but few studies have investigated the developmental mechanisms creating its diversity. To gain insights into the mechanisms, in this review article, we compared the pattern of cranial osteogenesis, temporal region histogenesis, and the expression of two key osteogenic genes, Runx2 and Msx2, in the temporal region between representative extant reptilian embryos.